Whole-exome sequencing analysis of NSCLC reveals the pathogenic missense variants from cancer-associated genes. (September 2022) - Kumar S, Udhaya; Balasundaram, Ambritha; Cathryn R, Hephzibah; Varghese, Rinku Polachirakkal; R, Siva; R, Gnanasambandan; Younes, Salma; Zayed, Hatem; Doss C, George Priya
Abstract: Background: Non-small-cell lung cancer (NSCLC) is the most common type of lung cancer. NSCLC accounts for 84% of all lung cancer cases. In recent years, advances in pathway understanding, methods for discovering novel genetic biomarkers, and new drugs designed to inhibit the signaling cascades have enabled clinicians to personalize therapy for NSCLC. Objectives: The primary aim of this study is to identify the genes associated with NSCLC that harbor pathogenic variants that could be causative for NSCLC. The second aim is to investigate their roles in different pathways that lead to NSCLC. Methods: We examined exome-sequencing datasets from 54 NSCLC patients to characterize the variants associated with NSCLC. Results: Our findings revealed that 17 variants in 14 genes were considered highly pathogenic, including CDKN2A, ERBB2, FOXP1, IDH1, JAK3, KMT2D, K-Ras, MSH3, MSH6, POLE, RNF43, TCF7L2, TP53, and TSC1 . Gene set enrichment analysis revealed the involvement of transmembrane receptor protein tyrosine kinase activity, protein binding, ATP binding, phosphatidylinositol-4, 5-bisphosphate 3-kinase, and Ras guanyl-nucleotide exchange factor activity. Pathway analysis of these genes yielded different cancer-related pathways, including colorectal, prostate, endometrial, pancreatic, PI3K-Akt signaling pathways, and signaling pathways regulating pluripotency of stem cells. Module 1 from protein-protein interactions (PPIs) identified genes that harbor pathogenic SNPs. Three of the most deleterious SNPs are ERBB2 (rs1196929947), K-Ras (rs121913529), and POLE (rs751425952). Interestingly, one patient has a pathogenic K-Ras variant (rs121913529) co-occurred with the missense variant (rs752054698) in TSC1 gene. Conclusion: This study maps highly pathogenic variants associated with NSCLC and investigates their contributions to the pathogenesis of NSCLC. This study sheds light on the potential applications of precision medicine in patients with NSCLC. Graphical abstract: Image 1 Highlights: In this study, we identified highly pathogenic variants and explored their roles in NSCLC development and proliferation. Our findings revealed that 17 nsSNPs located in 14 genes were considered highly pathogenic mutation. WES analysis also revealed that pathogenic K-Ras mutation G12V co-occurred with the missense (Y704C) from TSC1.